Kesiapan Mahasiswa Bidang Ilmu Pendidikan dalam Mengikuti Program Merdeka Belajar Kampus Merdeka - Ubaidillah, Endra; Prestiadi, Dedi; Adha, Maulana Amirul; Maulina, Sasi; Firdausi, Aulia Nur; Husna, Arumia Fairuz; Sari, Luthfia Amanda; Erviana, Yunita (Universitas Negeri Malang, 2024)
Abstract: This research is oriented towards the problem of implementing the MBKM program which has not been fully and properly addressed by all students in Indonesia. Extra preparedness is the keyword for the successful implementation of the MBKM program. The purpose of this study was to look at the level of student readiness in participating in the MBKM program which was approached quantitatively. Data analysis was carried out using a descriptive technique with the help of SPSS 24. The results showed that there was one MBKM program that had a very high level of student readiness, namely teaching assistance in educational units, four MBKM programs had a high level of student readiness, namely, student exchange, apprenticeship/work practice, entrepreneurial activities, and building a thematic real work village/college, three MBKM programs have a low level of student readiness namely research, humanitarian projects, and independent studies/projects. Keywords: student readiness, MBKM program, faculty of education Abstrak: Penelitian ini berorientasi pada problem penerapan program MBKM yang belum disikapi secara utuh dan baik oleh seluruh mahasiswa di Indonesia. Kesiapan ekstra menjadi kata kunci untuk keberhasilan penyelenggaraan program MBKM. Tujuan penelitian ini adalah melihat tingkat kesiapan mahasiswa dalam mengikuti program MBKM yang didekati secara kuantitatif. Analisis data dilakukan dengan teknik deskriptif dengan bantuan SPSS 24. Hasil penelitian menunjukkan terdapat satu program MBKM yang memiliki tingkat kesiapan mahasiswa sangat tinggi yakni asistensi mengajar di satuan pendidikan, empat program MBKM memiliki tingkat kesiapan mahasiswa tinggi yakni, pertukaran pelajar, magang/praktik kerja, kegiatan wirausaha, dan membangun desa/kuliah kerja nyata tematik, tiga program MBKM memiliki tingkat kesiapan mahasiswa rendah yakni penelitian/riset, proyek kemanusiaan, dan studi/proyek independen. Kata Kunci: kesiapan mahasiswa, program MBKM, fakultas ilmu pendidikan